Layout Optimization of AMAN Osing’s Marketing Media and Promotion - Dominikus Aditya Fitriyanto; Virginia Mandasari; Fairuz Mutia (Nusantara Science and Technology Proceedings, 2022)
An initiative to preserve the Osing cultural practices led to the creation of the Alliance of Indigenous Peoples of the Archipelago (AMAN) Osing. Due to unfavorable circumstances, AMAN Osing experiences revenue instability and must come up with creative solutions to continue performing normal tasks like their traditional school called ‘Pesinauan Isuk’. After observing AMAN Osing's efforts for some time, it has become clear that (1) marketing is still not at its best; (2) there are few ways to promote to the vast community; and (3) there is little room for movement because of Covid-19 and scarce resources. Given the issues AMAN Osing is experiencing, assistance is required to fix these issues. Following a discussion, it was determined which issues needed to be fixed right away. The proper use of public space and recognizing the best promotion tools are the top problems that need to be solved. The product of this mentorship activity is publishing in mass media, which creates modules for all socializing participants to better comprehend the existence of published journals about this activity, design ideas for suitable public locations, and the best promotional channels to use.